2021
DOI: 10.1002/ente.202100221
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Hydrogenation of Ring‐Strained Monoterpenes: A Route to High‐Performance Sustainable Aviation Fuels

Abstract: Sabinene and 3‐carene, bio‐based monoterpene precursors to high‐performance jet fuels, are chemoselectively hydrogenated with reduced PtO2 at low temperatures (263–298 K), to yield products in which the alkene groups are saturated, whereas cyclopropane rings from the parent hydrocarbons are conserved. Sabinene is selectively converted to a 79:21 mixture of cis:trans‐thujane (1), whereas 3‐carene is converted to a 72:28 mixture of cis:trans‐carane (3). For comparison, the fully hydrogenated species tetrahydrosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Meanwhile, on the premise of meeting indoor needs, redundant BVOCs can be considered by some methods of enrichment and transformation and the recovery of MAPs [ 74 ], research and development of new fuels [ 75 ] or hybrid fuels [ 76 ] and applications in other fields, such as gas-powered nanosynthesizers for automatic production of polymers on demand [ 77 ].…”
Section: Theoretical Method: Theoretical Design Scheme Of the Apehe S...mentioning
confidence: 99%
“…Meanwhile, on the premise of meeting indoor needs, redundant BVOCs can be considered by some methods of enrichment and transformation and the recovery of MAPs [ 74 ], research and development of new fuels [ 75 ] or hybrid fuels [ 76 ] and applications in other fields, such as gas-powered nanosynthesizers for automatic production of polymers on demand [ 77 ].…”
Section: Theoretical Method: Theoretical Design Scheme Of the Apehe S...mentioning
confidence: 99%
“…All chemicals were used as received. 1 H NMR spectra were collected as previously described 24 and are displayed in Figures S4 , S6 , S8 , S10 , and S 11 . Experimental parameters for GC-FID, GC-MS, and the measurement of kinematic viscosity, density, and heat of combustion are included in the Supplementary Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Terpenes have also been studied as precursors to high-density fuels for rocket and missile propulsion. This was accomplished through a variety of techniques including dimerization 22 , 23 , chemoselective hydrogenation of ring-strained terpenes 24 , and cyclopropanation 19 . Recent work by Harvey et al demonstrated that pinene, limonene, and sabinene, once hydrogenated, could be blended with synthetic paraffinic kerosenes to generate jet fuel that exceeded Jet-A standards 14 .…”
Section: Introductionmentioning
confidence: 99%
“…1 H NMR spectra were collected as previously described. 72 1 H and 13 C NMR spectra for the products described below as well as experimental parameters for GC-FID, GC-MS, and the measurement of kinematic viscosity, density, and heat of combustion are included in the Supporting Information.…”
Section: ■ Introductionmentioning
confidence: 99%